Implementation of Teacher Work Culture Development Policy in Secondary Education in Banten Province - Kamal Alamsyah; Lukman Lukman; Uyat Suyatna (Pasundan Social Science Development, 2022)
The main problem in this research is motivated by the existence of teacher development policies which tend not to work effectively. Even though the Provincial Government of Banten has issued Banten Governor Regulation Number 8 of 2014 concerning the Organization of the Teacher Work Culture Development Center (P2BKG). P2BKG tends not to be used effectively. The method used in this research is a qualitative research method with a descriptive approach. The results of the study revealed that the implementation of the policy for organizing the teacher work culture development center (P2BKG) had not been running effectively. The causative factors are: (1) the content of the policy which consists of: (a) the interests affected (interest affected) the implementation of the policy on the implementation of the teacher work culture development center; (b) the type of benefits in the implementation of the policy for organizing a teacher work culture development center; (c) the degree of change to be achieved (extent of change envision); (d) the location of decision making (site of decision making) for leadership in the implementation of the policy of implementing a teacher work culture development center; (e) implementing the program (program implementer) for organizing a teacher work culture development center; (f) the resources involved (resources committed) in the organization of work culture development centers. (2) the implementation environment (Context of Implementation) consists of: (a) the power, interests, and strategies of the actors involved; (b) institutional and regime characteristics; and (c) the level of compliance and response from employees (compliance and responsiveness) in the implementation of the teacher work culture development center. The strategy for implementing the policy for implementing a teacher work culture development center (P2BKG) in improving the quality of teachers and education staff, namely: (a) increasing professional resources by optimizing the availability of buildings and facilities to make it easier for teachers to implement programs to improve the quality of teachers and education staff held at the central development of teacher work culture; (b) optimizing professional resources by building a strong organizational structure supported by a shared commitment to implementing teacher quality improvement programs held at the teacher work culture development center. The two alternative strategies can be implemented in government policies based on the two dimensions of Grindle's theory, namely the content of policy and the context of implementation.